2017
DOI: 10.5455/jtomc.2017.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of hashimotos thyroiditis with papillary thyroid carcinoma: a single center experience

Abstract: Aim: A positive correlation between Hashimoto's thyroiditis (HT) and papillary thyroid cancer (PTC) is determinated in studies based on histopathological examination of the thyroidectomy materials, but this correlation is not determinated in studies based on Fine Niddle Aspiration Biopsy (FNAB). In this study, the histopathologic results of bilateral total thyroidectomy (TT) specimens were studied for outcomes of PTC association with HT and its relationship with clinical and pathological prognostic factors. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…After exclusion of duplicate articles, the literature search strategy identified 3597 potentially eligible articles. A total of 36 articles met the inclusion criteria, that is, their main purpose was to compare the prevalence of PTC in two groups of surgical specimens, categorized according to the presence or absence of histological changes compatible with CLT; however, 11 articles were excluded in which, after a thorough review of their methodology, it was possible to conclude that not all the specimens available during the study period were included in the statistical analysis [36][37][38][39][40][41][42][43][44][45][46] ; on the other hand, in three of the articles [47][48][49] , despite the inclusion of all the specimens available during the study period, after the application of the Chi-square test, the count of expected phenomena was lower than the minimum, which suggested that the sample assessed could be insufficient to perform an inferential analysis, which is why they were excluded. Finally, 22 articles 50-71 were included in which, in addition to meeting the inclusion criteria, it was possible to perform an inferential analysis, with the lowest possible source of selection bias (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…After exclusion of duplicate articles, the literature search strategy identified 3597 potentially eligible articles. A total of 36 articles met the inclusion criteria, that is, their main purpose was to compare the prevalence of PTC in two groups of surgical specimens, categorized according to the presence or absence of histological changes compatible with CLT; however, 11 articles were excluded in which, after a thorough review of their methodology, it was possible to conclude that not all the specimens available during the study period were included in the statistical analysis [36][37][38][39][40][41][42][43][44][45][46] ; on the other hand, in three of the articles [47][48][49] , despite the inclusion of all the specimens available during the study period, after the application of the Chi-square test, the count of expected phenomena was lower than the minimum, which suggested that the sample assessed could be insufficient to perform an inferential analysis, which is why they were excluded. Finally, 22 articles 50-71 were included in which, in addition to meeting the inclusion criteria, it was possible to perform an inferential analysis, with the lowest possible source of selection bias (Figure 1).…”
Section: Resultsmentioning
confidence: 99%